The computer analysis of primary structures for inulinases from various producers - V. G. Artyukhov (Компьютерные исследования и моделирование, 2011)
It is shown that the basic amount of homologous parts at inulinases from various species is presented by Gln, Asn and Glu residues. Carboxyl groups of Asp and Glu side chains (a part of active center of inulinase) can play the role of contact groups for substrate molecules and also carry out acid-base catalysis. Comparison of primary structures of inulinases has shown that frequency of residue substitution is very variable along the polypeptide chain. The phylogenetic tree of inulinases from various sources is constructed. It is revealed that high homology degree is characteristic for enzymes from Aspergillus awamori, Aspergillus niger and Aspergillus ficuum. Rather small relation degree is shown for endo- and exo-inulinases.